AUTONOMOUS MAINTENANCE UNTUK MENINGKATKAN PRODUKTIVITAS PRODUKSI DI PILOT LINE FACTORY 4 - Budihardjo, Iwan; Marisa, Dian (Industrial and Systems Engineering Assessment Journal (INASEA), 2009)
Sophisticated machinery can only demonstrate its superiority during the production process, while its operation and maintenance still depend on human skills and a good maintenance system. Total Productive Maintenance (TPM) can be applied to raise company productivity without abandoning scheduled machine maintenance. The purpose of this research is to improve the productivity of production on line stitching. The method used to increase the productivity of production is to calculate Overall Equipment Effectiveness (OEE), using the histogram of downtime, regression equations and correlation, the calculation of the cost of downtime, and analysis of the causes using a Plan, Do, Check, Action (PDCA). The survey results revealed the low productivity of the OEE calculation of 68.12%, due to the often damaged machine and duration of repairs. These in turn is caused by the lack of machinery maintenance, and unavailability of spare-part. To increase the percentage of OEE it is recommended to apply Autonomous Maintenance, building a spare-parts warehouse in every factory, increasing the number of stand-by engines, and provide training on procedures for the use of machinery in accordance with the appropriate Standard Operation Procedures (SOPs).